Missing Teeth and Prosthetic Treatment in Patients Treated at College of Dentistry, University of Dammam. (30th July 2017) - Fouda, Shaimaa M.; Al-Harbi, Fahad A.; Khan, Soban Q.; Virtanen, Jorma I.; Raustia, Aune
Abstract : The percentage of completely and partially edentulous patients and their prosthetic treatment at the Department of Substitutive Dental Sciences (SDS), College of Dentistry, University of Dammam, were investigated. Panoramic radiographs and medical records of adult patients (n = 479, mean age 45.9 years, and range 25–96 years) treated in 2011–2014 were examined. 6% of the patients were completely edentulous, 8% had single jaw edentulousness, and 74% were partially edentulous. Edentulousness was significantly correlated with age and the number of missing teeth was significantly higher among males (p < 0.026 ). Diabetes was significantly associated with complete edentulousness, single edentulous jaw (p value 0.015), and partial edentulousness (p value 0.023). Kennedy class III was the most frequent class of partial edentulousness in single and/or both jaws (p = 0.000 ). Patients having class I and/or class II were treated most often with removable partial dentures (RPD) (p = 0.000 ), while patients having class III were treated with fixed partial dentures (FPD). It was found that complete edentulousness increases in older age and the number of missing teeth was significantly higher among males. Kennedy class III was most common in both upper and lower jaw and was treated more often with FPD than with RPD.